Pendampingan Belajar Bahasa Arab dan Bahasa Inggris pada Anak-anak melalui Metode Games di Kabupaten Sinjai - Rosmita Rosmita (WAHATUL MUJTAMA': Jurnal Pengabdian Masyarakat, 2022)
Sinjai Regency is one of the Level II Regions in the province of South Sulawesi, Indonesia. The district capital is located in Sinjai, which is about ±220 km from Makassar City. The purpose of the STIBA Makassar Real Work Lecture (KKN) batch V is as a form of community service which is a pillar of the Tri Dharma of Higher Education. The method of implementing the service program begins with mapping the problems and needs of the community using SOAR analysis. After the analysis was carried out, the main program was arranged in the form of teaching Arabic and English as well as supporting work programs in the form of Social Service, Muslimah Taklim Council, and Teaching of the Qur'an, DIROSA and TK/TPA. All of these programs managed to run well and have shown initial results in accordance with the KKN objectives that have been proclaimed.